Association of Research Libraries records - Association of Research Libraries
Correspondence, memoranda, minutes of meetings, reports, financial records, printed matter, and other records relating to the association's membership and its assessment and evaluation projects and services on behalf of client institutions. Documents projects administered by the association including the Farmington Plan, Public Law 480 program, Foreign Newspaper Microfilm Project, and publication of the first Library of Congress catalog initiated and sponsored by the association.
Association formed in 1932 for the purpose of improving the collections and services of its member libraries in support of higher education and research. Consists of large university libraries; research libraries in the United States and Canada, including the three national libraries of the United States: the Library of Congress, the National Agricultural Library, and the National Library of Medicine; and public and special libraries with large research collections.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Farmington Plan; Library of Congress; National Agricultural Library (U.S.); National Library of Medicine (U.S.); Academic libraries; Acquisition of foreign publications -- United States; Agricultural libraries; Cooperative acquisition of library materials; Education, Higher; Libraries -- Societies, etc; Libraries -- Canada; Libraries -- United States; Library catalogs; Medical libraries; National libraries; Newspapers on microfilm; Public libraries; Research; Research libraries; Special libraries